PENJUALAN OKSIGEN PT.REZEKI SURYA GASINDO BERBASIS WEB - Riswan, Riswan; -, Nilawati; -, Sherli (LP2M Universitas Nurdin Hamzah, 2024)
Oxygen is one of the medical gases that is very much needed in hospitals as a life-supporting element that has a direct influence on maintaining patient life and most forms of life on earth to survive. The purpose of this study is to develop a cashier application information system for oxygen sales at PT. Rezeki Surya Gasindo, which is engaged in the distribution of oxygen in Jambi province. The oxygen sales system at PT. Rezeki Surya Gasindo was previously carried out manually, the company faced major problems, namely administrative errors, transaction recording and manual calculations. The cashier application information system is designed to replace the manual recording method with a web-based system. This system is built using the PHP programming language and MySQL database and uses qualitative methods. It is hoped that further researchers can further develop applications according to the company's needs in the future.